Microglia dynamic response and phenotype heterogeneity in neural regeneration following hypoxic-ischemic brain injury - Quan, Hongxin; Zhang, Runrui (Frontiers in Immunology, 2023)
Hypoxic-ischemic brain injury poses a significant threat to the neural niche within the central nervous system. In response to this pathological process, microglia, as innate immune cells in the central nervous system, undergo rapid morphological, molecular and functional changes. Here, we comprehensively review these dynamic changes in microglial response to hypoxic-ischemic brain injury under pathological conditions, including stroke, chronic intermittent hypoxia and neonatal hypoxic-ischemic brain injury. We focus on the regulation of signa ling pathways under hypoxic-ischemic brain injury and further describe the process of microenvironment remodeling and neural tissue regeneration mediated by microglia after hypoxic-ischemic injury.